PREVALENCE OF HIDDEN HUNGER (MICRONUTRIENT DEFICIENCY) AMONG THE HANDLOOM WEAVERS IN WESTERN ODISHA (The Journal of Research ANGRAU, 2023)
The objective of the research was to assess the prevalence of hidden hunger (micronutrient deficiency) among the handloom weavers of western Odisha. A sample size of 320 comprising of 170 male and 150 female respondents were selected randomly from four villages of Ulunda and Birmaharajpur blocks of Odisha in the year 2019-2020. The results indicated that the majority of male (58.23%) and female (50%) weavers had normal Body Mass index. Both male and female respondents had low vitamin A, vitamin C, calcium, and iron intake in comparison to RDA(Recommended Dietary Allowances) irrespective of all BMI categories. It was interesting to note that the thiamine, riboflavin, and sodium intake of both male and female weavers were found to be excess in comparision to RDA. Niacin intake of both male and female weavers was found to be excess in comparision to RDA for Obese-II respondents i.e. 8.55% and 7.57%, respectively. No significant mean difference between actual zinc and potassium intake of the respondents in comparision to RDA, ICMR Gopalan et al. (2016) was found in this study